Upregulation of IBSP Expression Predicts Poor Prognosis in Patients With Esophageal Squamous Cell Carcinoma - Wang, Mingyue; Liu, Baoxing; Li, Dan; Wu, Yufeng; Wu, Xuan; Jiao, Shuyue; Xu, Cong; Yu, Sheng; Wang, Shuai; Yang, Jianwei; Li, Yanmei; Wang, Qiming; et al. (Frontiers in Oncology, 2019)
Esophageal squamous cell carcinoma (ESCC), which is characterized by invasiveness and poor prognosis, is the sixth most common leading cause of cancer-related death worldwide. Despite advances in multimodality therapy, ESCC mortality remains high, and an understanding of the molecular changes that lead to ESCC development and progression remains limited. In the present study, Integrin Binding Sialoprotein (IBSP) upregulation was found in 182 of 269 (67.7%) primary ESCC cells at the mRNA level by quantitative real-time polymerase chain reaction (qRT-PCR). Additionally, IHC staining further demonstrated that IBSP was upregulated in ESCC patients and IBSP protein upregulation was significantly related to the lymph node metastasis (P=0.017), clinicopathologic stage (P=0.001) and poor disease survival (P=0.002). Moreover, functional studies illustrated that the IBSP gene can promote the proliferation and metastasis of ESCC cells. Furthermore, IBSP was found to regulate epithelial-mesenchymal transition (EMT), which promotes tumor cell metastasis. In conclusion, our study suggests that IBSP may be a valuable prognostic marker for ESCC patients.